Upaya Women Migrant Workers Filipina dalam Realisasi Agenda SDG 8 Periode 2017-2019 - Gibran Fakhrishan; Nurmasari Situmeang; Sindy Yulia Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe how the efforts of Women Migrant Workers in helpingto alleviate poverty are reviewed through SDG 8 as an indicator of the success ofthe government's reciprocal relationship regarding the rights and protections thatthey have and should get during the 2017-2019 period. To discuss this problem, theresearcher uses a framework of thought through feminism theory of internationalpolitical economy, migration theory, compliance theory, and also the concept ofnon-state actor. The results of this study indicate that Women Migrant Workershave succeeded in sending 19.2% of the total remittances during that period.However, their rights and protection have not been addressed through a review ofSDG 8. For internal factors, SDG 8 cannot fulfill its objectives optimally becauseits position is not stronger than national law. Then externally, WMWs recipientcountries have their own regulations in handling the migration process, so thatgender-sensitive migration conditions have not been realized. Keywords: Women Migrant Workers, Philippines, Poverty, SDG 8, Rights andProtections